2007
DOI: 10.1135/cccc20071676
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Functional Derivatives of 7,8-Dicarba-nido-undecaborate Anion by Ring-Opening of Its Cyclic Oxonium Derivatives

Abstract: A new approach to synthesis of functional derivatives of 7,8-dicarba-nido-undecaborate anion based on ring-opening of its cyclic oxonium derivatives [10-(CH 2 ) 4 O-7,8-C 2 B 9 H 11 ] and [10-O(CH 2 CH 2 ) 2 O-7,8-C 2 B 9 H 11 ] with various nucleophiles was developed. Both cyclic oxonium derivatives can be obtained as single isomers by reaction of the parent anion [7,8-C 2 B 9 H 12 ] -with mercury(II) chloride in the corresponding solvents. Mechanism of formation of the cyclic oxonium derivatives of 7,8-dicar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…[19] An analogous approach, but using ethyl alcohol instead of dimethylformamide as a reaction medium, was published recently by other authors. [20] Table 1 summarizes the characteristics of compounds 2-6, 7, and 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] An analogous approach, but using ethyl alcohol instead of dimethylformamide as a reaction medium, was published recently by other authors. [20] Table 1 summarizes the characteristics of compounds 2-6, 7, and 8.…”
Section: Introductionmentioning
confidence: 99%
“….55 (s, B8'), 0.35 (s, B10'), À2.51 (s, B10 overlap), À4.48 (s, B4',7'), À7.26 (s, B9',12'), À8.12 (s, B9,12), À17.34 (s, B5',11'), À20.39 (s, B5,11), À22.10 (s, B6' overlap), À28.62 ppm (s, B6); MS (FAB, Gly, -ve,): m/z (%): calcd for C 20 …”
mentioning
confidence: 99%
“…Eleven vertex 7,8-Dicarba-nido-dodecahydroundecaborate(1−) ion [1] belongs to the most studied boron cluster anions due to its easy availability from ortho-carborane [2], open pentagonal C 2 B 3 plane with three stereochemically distinctive sites for substitution and an extra hydrogen atom sitting on it [3,4]. It is well recognized that the coupling of the [nido-7,8-C 2 B 9 H 12 ] − ion with tetrahydrofuran and dioxane promoted by various metal halides, such as FeCl 3 [5] or HgCl 2 [6,7], yields the neutral zwitterionic compounds [10-(CH 2 ) 4 O)-nido-7,8-C 2 B 9 H 11 ] or [10-(O-(CH 2 -CH 2 ) 2 O)-nido-7,8-C 2 B 9 H 11 ] (1). More recently, we reported that the dioxane derivative 1 can be produced in high yield by reaction of the neutral carborane nido-C 2 B 9 H 13 with dioxane used as solvent [8].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the ring cleavage methodology brings a level of high versatility to a broad scope of applications. Furthermore, the resulting substituents are located on the cage in a symmetrically located position and hence the products are free from stereochemical complications such as the presence of diastereoisomeric pairs or chirality [7]. The compound, and its derivatives arising from ring cleavage, can potentially serve as new charge-compensated [41,42] or common type of ligands in the synthesis of metallacarboranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation